The Effect of Different Type Drying Methods on Chemical Characteristics and Microbiology of Goat Milk Powder Kefir - Nurwantoro Nurwantoro; Siti Susanti; Heni Rizqiati (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2020)
The research aims to test and compare the chemical characteristics and total Lactic Acid Bacteria or LAB of goat milk powder kefir that was produced from cabinet drying, freeze drying and spray drying. Kefir was made from goat milk since it was found as a good digestibility, no β-lactoglobulin, and high protein. Data analysis was performed with the test analysis of variance with a significance level of 5% followed by Duncan testing if significant result was detected. Analysis of total acid was conducted using titration. Analysis of proteins was conducted using Kjeldahl method. Water content analysis was performed using oven and ash content was analyzed using furnace. Analysis of fat content was conducted using Soxhlet method. Analysis of total LAB and total yeast were done using Total Plate Count (TPC). As results, drying method significantly affected (p<0.05) water content, ash content, and total LAB but there was no significant effect (p<0.05) on the total acid, protein content, fat content, and total yeast. As conclusion, the best treatment of drying method in making goat milk kefir powder was spray drying